Mitigating Postfrying Degradation Factors of Fats and Oils through the Development of Bagasse-Based Adsorbent - Waqar Ahmed; Muhammad Asim Shabbir; Rana Muhammad Aadil; Muhammad Anjum Zia; Anubhav Pratap-Singh (Journal of Food Quality, 2023)
The quality of fats and oils is a critical aspect of the food processing industry and consumer health. Fat degradation, particularly through oxidation, impacts various quality parameters, including color, taste, flavor, aroma, quality, and appearance. To address this issue, a study was conducted using five degraded fats/oil (DF/O) commodities as the target for an adsorption process. These commodities were chosen because of their high level of degradation by-products. The study used sugarcane bagasse (SCB) to develop five different treatments of indigenous adsorbents activated with various NaOH concentrations. Analyses including iodine number, adsorbent yield, and scanning electron microscope were performed to identify the potential of the prepared concentrations. Results showed that the indigenous adsorbent created with 1.0% NaOH was the most effective. The alkali treatment had a positive impact on the samples, but the SCB 10% was found to be the most efficient in reducing the degradation value of the treated samples. The findings of this study suggest that the use of indigenous adsorbents, particularly those prepared with SCB 10%, can be an effective way to reduce fat degradation and enhance the quality of fats and oils in the food processing industry. This approach can also address consumer health concerns related to fat and oil quality.